Analysis of Optimum Speed of ROLA Transportation with Flat Cars (GD 400910) on the Minimum Curve of the PPI Madiun Track Using Universal Mechanism Software - Dadang Sanjaya Atmaja; Mohamad Imron Mustajib; Dimas Adi Perwira; Ilham Satrio Utomo; Henry Widya Prasetya; Destika Riski Putrihastiaji; Izza Anwer (Politeknik Perkeretaapian Indonesia Madiun, 2026)
An innovative solution for low-emission and environmentally friendly freight transport is the Rollende Landstraße (ROLA) train. Research at the Indonesian Railway Polytechnic (PPI) in Madiun conducted dynamic simulations to analyze safe operating speeds when crossing minimum curved tracks with a radius of 42 meters to prevent derailment. The simulation results show that the optimal speed limit for ROLA transport is 14 km/h for fully loaded trucks, 17 km/h for half-loaded trucks, and 19 km/h for unloaded trucks. This speed must be maintained constantly when passing through curves to ensure safety and comfort.